The influence of event order on the narratives jurors construct and tell in cases of rape - Lee, Harrison D. H. (Psychology, crime & law, 2024)
Rape victim testimony may seem incongruent with the ‘real rape’ stereotype and appear more consistent with typical consensual sex. This research investigated whether having victims describe stereotype-consistent events early in their testimony guides jurors to construct narratives of the evidence that are consistent with rape and depict the defendant as guilty. In Study 1, a convenience sample (N = 38, 65.79% female, 34.21% male) watched video testimony in which the victim described the details of the assault first or last, with participants verbalising their thoughts about the testimony as they watched. We then recorded participants’ spoken narratives about the alleged rape, which community members (N = 418, 41.15% female, 58.61% male, 0.24% gender-fluid) evaluated in Study 2. In Study 1, participants’ thoughts in the rape-first condition suggested they attended more to the victim’s non-verbal cues to deception than the events described. Consistent with this, participants in Study 2 rated the narratives of those in the rape-first condition as less complete. However, counter to predictions, participants’ perceptions of the narratives as typical of rape did not differ based on condition. Further, participants were less likely to find the defendant guilty after listening to the narratives of those in the rape-first condition.